Pembuktian dalam Unsur Menyembunyikan dan Menyamarkan dalam Perkara Tindak Pidana Pencucian Uang - Arya Ilham Ramadhanu (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Money Laundering is any criminal act that fulfills the elements of a criminal act as regulated in Law Number 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering. Proof is one of the procedures that must be carried out in the Criminal Procedure Law, which will help find light on a criminal act. Due to the various types and methods in this criminal act, the evidence carried out is in accordance with the criteria and type, in this case the author wants to analyze the elements of hiding and disguising the crime of money laundering. The research method used is a normative-empirical approach using a statutory approach. The research results show that 1) Money laundering is considered a serious criminal act because it can support other criminal activities such as drug trafficking, terrorism, corruption and organized crime; 2) Proof in criminal procedural law is the process of showing the truth of accusations or accusations made in a criminal case. 3) Proving the crime of money laundering requires cooperation between various institutions and the use of technology and special expertise to analyze complex financial transactions. In this way, it is hoped that the judicial process can run transparently and fairly, and ensure that money laundering crimes can be punished appropriately.